Performance evaluation of aeroderivative gas turbine models derived from a high bypass turbofan for industrial power generation. Issue 1 (1st January 2017) - Effiom, Samuel O.; Abam, Fidelis I.; Nwankwojike, Bethrand N.
Abstract: The paper presents the evaluation of the performance of various aeroderivative gas turbine models (AGTM) derived from a high bypass turbofan engine (HBTE). The objective of the study is to determine the performance and suitability of the developed AGTM for power generation. Furthermore, the models were specified as Model I (two shafts with FPT), Model II (two shafts with direct-drive LP turbine), and Model III (one shaft with FPT). The useful performance data for the AGTM was generated using the turbomatch simulation code. Additionally, the preliminary design point (DP) performance results estimated the power output and thermal efficiency of Models I, II, and III which ranged between 3.46 ≤ POT ≤ 10.67 MW and 29.8 ≤ η t h ≤ 38.1 % respectively. However, after the preliminary analysis, Model III failed the test based on performance and economic constraint while Models I and II were subjected to further performance study. The analysis indicates that Model II runs into surge at about 72% DP power and would require the installation of bleed valves or variable stator vanes for stability. Hence, additional production costs. Nonetheless, Model I was operationally stable at part-load conditions (< 110% DP Power) with no compressor surging. Based on the observed operational performance of the Models, Model 1 was best preferred and thus suggested for possible development.